SURVEY ON APPLICATION OF LAGRANGIAN RELAXATION, INTERIOR POINT AND DYNAMIC PROGRAMMING FOR THE SOLUTION OF HYDROTHERMAL SCHEDULING - Hashmi, I.; Umair, M.; Islam, N. U.; Haroon, S.; Nadeem, T. (The Nucleus, 2013)
This paper provides a critical analysis of research work published on the topic Hydro thermal Coordination problem using Lagrangian Relaxation, Interior Point, and Dynamic Programming. The HTS is a large scale, mixed integer, complex, and nonlinear problem. Lagrangian Relaxation fails to find feasible solution. Moreover, it doesnâ€™t converge to global minima. Interior Point uses the interior of a given solution instead of using the vertices. Dynamic Programming requires long computation time and storage memory. In addition there is also one more drawback of DP is â€œcurse of dimensionalityâ€. The drawbacks of these techniques are resolved by the usage of modern techniques like, coevolutionary, differential co-evolutionary, stochastic programming, GA, BFA, and PSO etc. At the end a conclusion has been presented based on the literature survey.